Prototyping as an augmented reality resource to aid dental practice (Research, Society and Development, 2023)
Initially used in engineering, rapid prototyping assists in the exact and faithful reproduction of objects for structural planning and architectural evaluation of projects. With the advancement of technology, this technique began to be used in the health area, allowing the creation of models used for planning and customized parts according to the needs of each individual, providing benefits to the surgeon and the patient. This work aims to identify and characterize the main forms of prototyping in dentistry and their applications in this area. From this, an exploratory, qualitative and bibliographic methodology was used in the Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS) and National Center for Biotechnology Information (PubMed) databases. Thus, an advanced search methodology was used through Boolean descriptors, inserting complete articles, published between the years 2018 to 2023 in Portuguese, English and Spanish. Based on this, it is concluded that prototyping brings satisfactory and beneficial results for the surgeon who has the possibility of individualized planning and with the aid of the 3D model, which makes a tactile planning, also for the patient who enjoys a resource in which he can get a piece tailored to their case.